Billboard Advertisement and Racial Perception in Ghana - Pauleson A. Utsu (E-Journal of Humanities, Arts and Social Sciences, 2022)
This paper examines why business people in Ghana prefer using images of white people on their billboard outdoor advertisements. To attain the study’s objective, a cross-sectional survey was used. Data was collected from only a section of retail and wholesale businesses within the Ejisu and Juaben districts in the Ashanti Region of Ghana which use images of white people on their billboard outdoor advertisement. The survey findings show that retail and wholesale businesses use images of white people on their outdoor billboard advertisements because they are more attractive than images of black people. Also, the use of images of white people indicates a seal of professionalism, desirability, and quality services. The survey’s discovery reveals the racial perceptions of the white race in comparison with the black race by most African business people. The usage of the images of white people as the symbolic representation of ideal beauty, attractions, quality products and services, and model of authentic marketization has unfolded some of the factors that stymie the utilization of the images of the black people on an outdoor billboard advertisement. This paper contends that there is a necessity for a balanced moral reasoning and constructive racial perception of images of black people and self-identification.